Dual quaternions for the kinematic description of a fish-like propulsion system - Kitowski, Zygmunt; Piskur, Paweł; Orłowski, Mateusz (Zielona Góra: Uniwersytet Zielonogórski)
This study discusses the use of quaternions and dual quaternions in the description of artificial fish kinematics. The investigation offered here illustrates quaternion and dual quaternion algebra, as well as its implementation in the software chosen. When it comes to numerical stability, quaternions are better than matrices because a normalised quaternion always shows the correct rotation, while a matrix more easily loses its orthogonality due to rounding errors and oversizing.
Keywords: quaternions; dual quaternions; artificial fish; underwater vehicle; undulating propulsion system